Aplicações dos princípios da gestão estratégica no Sistema de Bibliotecas da Universidade Federal do Ceará - Damasceno, Kécia Silva (2012)
Planning is a natural activity that frequently is intuitive in people’s lives; but, referring to the management of such a important sector as the University Library, which is essential to the development of teaching, researching and extension activities, we need the use of a structured management method through which it would be possible to make sure that the traced strategies can be translated into operational terms. The application of the principles of the Strategic Management in University Libraries was studied with an aim to evaluate if they really do exist and what are the methods of planning adopted by part of the managers of the System of Libraries (SB) the Federal University of Ceará (UFC). In this manner, they contribute, along with the presentation, a route of Strategic Planning with possible applications to the UFC System of Libraries. Such a study bases itself in the bibliographical, documental and field research, qualitative. One technique utilized in the collection of primary data, were two questionnaires that were structured with open and closed questions, including opinion scale based in the measure of Likert, applied to the actual direction of the SB/UFC and to the managers of the UFC’s libraries. The obtained were transcribed into graphics to better visualize the incidence of the answers. The Strategic Management model adopted in university libraries is indicated because it is a management model proofed as compatible with the activities developed by this type of informational unity. It presents the retrospective results of studies realized by the SB/UFC’s work team in which the strategic confirms the viability of the adoption of this management method, having, by means of valuations of the actual conditions, the base of the view of facts and events, that are indicators of the future, related through the analysis of market potential Strengths Weaknesses Opportunities Treats (SWOT) matrix, of the referred System. One can affirm, therefore, that such management method demonstrates highly inspiring results, consolidating the growth of the organizational management learning, in the pursuit of achieving levels of excellence amid the constant changes and the adequacy of the use of human and material resources available for the development of sector, that has as aim to consolidate as a basis to the teaching, researching and extension, through the constant improvement of the provided services to the academic community inside and outside the UFC.